Breast reconstruction with autologous tissue - Fansa, Hisham; Heitmann, Christoph (SpringerLink Bücher, 2019)
This book describes the various techniques available for autologous breast reconstruction, be it breast conserving therapy (BCT) or reconstruction following total mastectomy with local and distant flaps. Divided into two parts, the first presents the anatomy of the breast and the general requirements with regard to this kind of surgery. In turn, the second addresses reconstructive breast surgery management. The authors present oncoplastic procedures for reconstructing the breast following small defects due to cancer or other conditions (BCT), as well as the use of microvascular free flaps, such as abdominal, thigh or gluteal-based flaps, for a complete reconstruction. Preventive reconstructive surgery and cutting-edge techniques, such as lipofilling or breast reconstruction together with lymph node transplantation, are also included. Written by leading international plastic surgeons and combining step-by-step explanations and detailed illustrations, this book clearly demonstrates that reconstructive procedures can have aesthetic outcomes